2022
DOI: 10.1111/1460-6984.12719
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for pre‐school children with co‐occurring phonological speech sound disorder and expressive language difficulties: A scoping review

Abstract: Background Recent evidence suggests that pre‐school children with co‐occurring phonological speech sound disorder (SSD) and expressive language difficulties are at a higher risk of ongoing communication and literacy needs in comparison with children with these difficulties in isolation. However, to date there has been no systematic or scoping review of the literature specific to interventions for children with this dual profile. Aims To explore the evidence regarding interventions for pre‐school children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Children did not improve the pronunciation of sounds. Similar problems were identified by other scholars on the use of speech therapy methods (Beukes et al, 2016;Rodgers et al, 2022;Vismara et al, 2018). The research found that to correct the pronunciation of sounds, it was important to introduce other techniques in computer programs and make use of standard speech therapy methods (Brown & Woods, 2015).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Children did not improve the pronunciation of sounds. Similar problems were identified by other scholars on the use of speech therapy methods (Beukes et al, 2016;Rodgers et al, 2022;Vismara et al, 2018). The research found that to correct the pronunciation of sounds, it was important to introduce other techniques in computer programs and make use of standard speech therapy methods (Brown & Woods, 2015).…”
Section: Discussionsupporting
confidence: 57%
“…Most scholars underline that children with poor visual-spatial skills and understanding of space designations have some specific factors: a low level of understanding and wrong ideas about space (Rodgers et al, 2022). This leads to delays in speech development and affects the quality of learning (Law et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The search will be conducted in Ovid Emcare, MEDLINE Complete, CINAHL, APA PsycINFO, ERIC and Communication Source. These sources have been selected as they encompass the fields of health (medical, nursing and allied health professions), speech and language therapy, education and psychology and have been successfully used in previous reviews in the field 26 40. To support literature saturation, supplementary search methods will be employed; this includes screening the reference lists from prominent reviews in the field post 2012 41 42.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Although this overlap exists between DLD and phonological SSDs, there is currently a paucity of theoretically informed interventions which have been specifically developed for this group 26. Additionally, intervention studies within existence primarily target morphosyntactic aspects of expressive language, alongside accuracy of speech sound production 26 27.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation